2023
DOI: 10.1039/d2fo03807b
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal iron bio-accessibility changes by Lignin and the subsequent impact on cell metabolism and intestinal microbiome communities

Abstract: The detrimental effects of high concentrations of colonic iron have been linked to intestinal inflammation and microbial dysbiosis. Exploiting chelation against this luminal pool of iron may restore intestinal health...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Indeed, this Fe chelating ability has also been associated with other insoluble fibre fractions. Thus, Horniblow et al [53] have recently shown in cell line models (RKO and Caco-2 cells) a significant decrease in intracellular Fe concentration and ferritin expression in the presence of lignin. In our study, we hypothesised that adsorption of Fe to insoluble cellulose also led to insolubilisation of this element in the gastrointestinal model proposed, thus decreasing Fe bioaccessibility.…”
Section: Cellulosementioning
confidence: 95%
“…Indeed, this Fe chelating ability has also been associated with other insoluble fibre fractions. Thus, Horniblow et al [53] have recently shown in cell line models (RKO and Caco-2 cells) a significant decrease in intracellular Fe concentration and ferritin expression in the presence of lignin. In our study, we hypothesised that adsorption of Fe to insoluble cellulose also led to insolubilisation of this element in the gastrointestinal model proposed, thus decreasing Fe bioaccessibility.…”
Section: Cellulosementioning
confidence: 95%
“…While the biopolymeric compound was safe and well tolerated, there were no changes to microbiota populations, and the iron-chelating ability of alginate was presumed to be confounded, possibly by the presence of other dietary chelators in the luminal food matrix content. Further published research by the same authors [ 31 ] showed that another biopolymer compound, namely, lignin, chelated iron and restricted its availability to detrimental proteobacteria while promoting the growth of favored beneficial bacteroides. Hence, lignin could be used to control microbial dysbiosis and inflammation associated with gut disorders.…”
mentioning
confidence: 99%